2010
DOI: 10.1017/s0954422410000193
|View full text |Cite
|
Sign up to set email alerts
|

Antisecretory factor as a potential health-promoting molecule in man and animals

Abstract: Antisecretory factor (AF) is a protein secreted in plasma and other tissue fluids in mammals with proven antisecretory and anti-inflammatory activity; its immunohistological distribution suggests a role in the immune system. The expression level and the distribution of AF protein are altered during an immunological response. Exposure to bacterial toxins induces secretion of AF in plasma, probably reflecting a natural defence mechanism to agents causing diarrhoea, thereby contributing to a favourable clinical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 108 publications
1
21
1
Order By: Relevance
“…We also demonstrated the involvement of several important cell membrane lipid species in response to SPC intake. This indicates that AF might form peptide-cell interactions with the cell membrane through the peptide exposure of active sites, thus supporting recent studies2555 on the ability of this feed to induce the endogenous production of AF in the body. The results might have significance to understanding the basic function of lipids in brain and cell function as well.…”
Section: Resultssupporting
confidence: 83%
“…We also demonstrated the involvement of several important cell membrane lipid species in response to SPC intake. This indicates that AF might form peptide-cell interactions with the cell membrane through the peptide exposure of active sites, thus supporting recent studies2555 on the ability of this feed to induce the endogenous production of AF in the body. The results might have significance to understanding the basic function of lipids in brain and cell function as well.…”
Section: Resultssupporting
confidence: 83%
“…; Ulgheri et al . ). Given these properties, AF has been used for treatment of diseases with imbalanced secretion, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Antisecretory factor (AF) is an endogenous 43 kDa protein that is expressed in all mammalian tissues and plasma investigated so far (Johansson et al, 1995, 2009; Lange et al, 1999; Lange and Lönnroth, 2001; Ulgheri et al, 2010). The protein was named AF due to its capacity to counteract enterotoxin-induced intestinal hypersecretion, but later studies have shown that AF is also a potent anti-inflammatory agent (Johansson et al, 1997a, 2013; Eriksson et al, 2003; Davidson and Hickey, 2004a,b; Graber et al, 2011; Mane et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The protein was named AF due to its capacity to counteract enterotoxin-induced intestinal hypersecretion, but later studies have shown that AF is also a potent anti-inflammatory agent (Johansson et al, 1997a, 2013; Eriksson et al, 2003; Davidson and Hickey, 2004a,b; Graber et al, 2011; Mane et al, 2011). Protein AF, which is also named S5a or RPn10, is a component of the 26S proteasome (Ulgheri et al, 2010). It can either be associated to the proteasome, or appear in a free form.…”
Section: Introductionmentioning
confidence: 99%